Sous couleur de jouer La métaphore ludique - Henriot, Jacques (Bibliothèque idéale des sciences sociales, 2023)
Sous couleur de jouer: the phrase comes from Claude Lévi-Strauss. It suggests that playful behaviour conceals its true essence. What is someone who is said to be playing doing? The starting point of this book is the refusal to take play for granted, as a way of being and doing that is immediately accessible and decipherable: the intention to consider it more as a mental attitude, an inner adventure that is almost impossible to grasp, that we can only identify, designate and describe through words. No one understands themselves, or makes themselves understood, except through ways of saying (and thinking) drawn from common experience. Pierre Corneille's Psyché, in her confusion, discovers this obvious fact: And I would say that I love you, Lord, if I knew what it is to love. So the player cannot say that he is playing, cannot say if he is playing-and first of all can only play if he knows what it is to play. In this strange roundabout way, the idea of play is more an anthropological approach than a psychological elucidation. When we set out to deal with the inexpressible, is it not appropriate, at least to begin with, to pay attention to what is said about it? Originally published by José Corti in 1989, and out of print for several years, Jacques Henriot's seminal work urgently needed to be republished, as much as a way of thinking about play as a way of criticising thinking that is too quick to analyse what makes play and, perhaps more importantly, the play itself.